ANTHROPOMETRIC CHARACTERISTICS AND ANAEROBIC POWER OF LOWER LIMBS AND THEIR RELATIONSHIPS WITH RACE TIME IN FEMALE SPEED CLIMBERS - Krawczyk, Marcin; Ozimek, Mariusz; Rokowski, Robert; Pociecha, Mariusz; Draga, Pawel (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Previous research indicates that high results in speed climbing are determined by a high level of explosive strength and muscle power in the lower limbs. However, a literature review shows that no studies have analysed women practicing this climbing discipline. Therefore, the main goal of the study was to assess the level of development of physique and the level of explosive strength and muscle power of the lower limbs of female speed climbers at a representative level. Furthermore, an attempt was made to analyse the relationships between the variables studied and race time in female speed climbers.The study included 5 female players (speed climbers) who were members of the national team in 2016. The measurements were made during the Polish National Team Camp. The analysis was based on the results of the fastest races expressed in seconds. The measurements and indices computed in the study included body height, body weight, lean body mass, BMI and ponderal index. The assessment of the power of the lower limbs was carried out using two jump tests: CMJ with arm swing and CMJ. Power was expressed relative to body weight and to lean body mass.The highest relationships with race time were recorded for body height (r = 0.94, p <0.05), body weight (r = 0.96, p <0.01) and lean body mass (LBM) ( r = 0.98, p <0.01). Strong but statistically insignificant relationships were recorded between race time and power indicators of the lower limbs (correlations above r = -0.66).In female speed climbing, race time can be determined by the level of physique. Smaller body size can allow female climbers to perform faster and achieve better times in speed climbing. It can be suggested that in female speed climbing, a high level of maximum alactic anaerobic capacity of the lower limbs is an important factor that affects race time. The results of our own research suggest that in female speed climbing, specific body characteristics may to a greater extent determine the race time compared to anaerobic maximum power of the lower limbs.